A BUU Code for Parallel Computers - Barbosa, V. C.; Donangelo, R.; Wedemann, R. S. (International journal of modern physics. C, Computational physics, physical computation, 1998)
We have developed a distributed algorithm for the simulation of systems that evolve continuously, but which are also subject to discrete events that affect their evolution. As an example we consider the description through the BUU equations of the time evolution of a highly excited nuclear system, and show that this algorithm attains almost optimal speedups.